ASPEK HUKUM PEMBERIAN IZIN PENGGUNAAN KENDARAAN DINAS DILINGKUNGAN SEKRETARIAT DAERAH KABUPATEN NIAS DIKAITKAN DENGAN PERATURAN PEMERINTAH NOMOR 27 TAHUN 2014 TENTANG PENGELOLAAN BARANG MILIK NEGARA/DAERAH - Apnes Perlindungan Zaro Hura; Pendastaren Tarigan; Jusmadi Sikumbang; Edy Ikhsan (Universitas Sumatera Utara, 2017)
ABSTRACT The use of official vehicles at the Regional Secretariat of Nias District from the administrative observation is viewed as the barometer to be followed by other agencies under the Nias District Government. The use of official vehicles is not in line with the official report because of lack of supervision by the state/regional-owned property management. The official vehicles used by the regional head, regional secretary, agency head, section head, and sections under the Regional Work Unit in the Regional Secretariat of Nias District are provided to aid and support their performances in carrying out their duties and work. The provision of license of official vehicles in the Regional Secretariat of Nias District was found out to be complicated and was inefficient, particularly on the application process for using the official vehicles for the applicants (Civil Servants) because there were so many approvals to get the license to use the official vehicles from the administrative structure of the organization in the Regional Secretariat of Nias District. Keywords : official vehicles, state/regional-owned property